ANALYSIS OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT GUNAWANGSA MANYAR APARTMENT IN SURABAYA - Muhammad Farrel Nugroho; Nuryadi Nuryadi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study aims to analyse the influence of work environment and work motivation on employee performance at Gunawangsa Manyar Apartment in Surabaya. Work environment and motivation are considered strategic factors that determine the effectiveness and productivity of human resources, especially in the service industry which demands high quality service. This study uses a quantitative approach with a descriptive method. Primary data were collected through a questionnaire distributed to 27 permanent employees using total sampling technique. The research instruments were tested for validity and reliability, then analysed using multiple linear regression assisted by SPSS. The results show that the work environment and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. The work environment variable is the most dominant factor affecting performance compared to work motivation. The coefficient of determination (R²) value of 0.901 indicates that 90.1% of the variation in employee performance is explained by these two variables. These findings emphasise the importance of managing a conducive work environment and implementing sustainable motivation enhancement strategies to optimise employee performance within the organisation.